2023
DOI: 10.3389/fpsyg.2023.1054707
|View full text |Cite
|
Sign up to set email alerts
|

Multifactorial structure of cognitive assessment tests in the UK Biobank: A combined exploratory factor and structural equation modeling analyses

Abstract: IntroductionThe UK Biobank cognitive assessment data has been a significant resource for researchers looking to investigate predictors and modifiers of cognitive abilities and associated health outcomes in the general population. Given the diverse nature of this data, researchers use different approaches – from the use of a single test to composing the general intelligence score, g, across the tests. We argue that both approaches are suboptimal - one being too specific and the other one too general – and sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…We applied Genomic SEM to GWAS summary statistics for 12 cognitive traits in the UKB and found that a three-factor model best explained the genetic correlations between the cognitive traits. This is consistent with findings from a previous study that applied structural equation modeling to phenotypic data from the UKB cognitive assessments and found that a three-factor solution fit the data best 32 . The three cognitive factors identified in the current study may be characterized using the framework provided by the Cattell–Horn–Carrol (CHC) theory of human cognitive abilities, which proposes a three-stratum model of human intelligence 24 , 33 .…”
Section: Discussionsupporting
confidence: 91%
“…We applied Genomic SEM to GWAS summary statistics for 12 cognitive traits in the UKB and found that a three-factor model best explained the genetic correlations between the cognitive traits. This is consistent with findings from a previous study that applied structural equation modeling to phenotypic data from the UKB cognitive assessments and found that a three-factor solution fit the data best 32 . The three cognitive factors identified in the current study may be characterized using the framework provided by the Cattell–Horn–Carrol (CHC) theory of human cognitive abilities, which proposes a three-stratum model of human intelligence 24 , 33 .…”
Section: Discussionsupporting
confidence: 91%
“…This is consistent with findings from a previous study that applied structural equation modeling to phenotypic data from the UKB cognitive assessments and found that a three-factor solution fit the data best. 45 The three cognitive factors identified in the current study may be characterized using the framework provided by the Cattell-Horn-Carrol (CHC) theory of human cognitive abilities, which proposes a three-stratum model of human intelligence. 44 46 Consistent with the relatively high genetic correlation between factor 1 and factor 2, the first two latent cognitive factors appear to capture the same broad cognitive ability, fluid reasoning ( Gf ).…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive tests used by the UK Biobank are not standardized and at the time of administration had not been tested for psychometric quality. Since then, psychometric quality of the UK Biobank cognitive tests has been assessed in several studies (Lyall et al, 2016;Fawns-Ritchie et al, 2020;Ciobanu et al, 2023).Psychometric quality in terms of internal consistency, short-term test-retest reliability and concurrent validity of the UK Biobank cognitive tests have been found to be reasonable to good in general (Lyall et al, 2016;Fawns-Ritchie, 2020), although the long-term test-retest reliability of some of the tests may not be ideal (Lyall et al, 2016).…”
Section: Cognitionmentioning
confidence: 99%